HOW TO IMPROVE CRITICAL THINKING SKILLS IN STUDENTS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Critical thinking is the ability to solve problems, make decisions, and analyze information. Improving students' critical thinking skills is critical to their academic success and future professional careers. In this article, we will talk about effective approaches and methods to improve students' critical thinking skills.